Acute aortic dissection with entry tear at the aortic arch: long-term outcome. (21st November 2020) - Koechlin, Luca; Schuerpf, Julia; Bremerich, Jens; Sommer, Gregor; Gahl, Brigitta; Reuthebuch, Oliver; Gurke, Lorenz; Mujagic, Edin; Eckstein, Friedrich; Berdajs, Denis A
Abstract: OBJECTIVES: The goal was to evaluate outcomes after conservative or surgical treatment of acute aortic arch dissections. METHODS: Between January 2009 and December 2018, patients with a diagnosis of acute aortic dissection were analysed. Aortic arch aortic dissection was defined as a dissection with an isolated entry tear at the aortic arch with no involvement of the ascending aorta. RESULTS: Aortic arch dissection was diagnosed in 31 patients (age 59 ± 11 years). Surgical intervention was performed in 13 (41.9%) cases. Overall in-hospital mortality was 3% ( n = 1), and all deaths occurred in the conservative group ( n = 1; 6%), whereas the overall stroke rate was 3% ( n = 1), and all strokes occurred in the group treated surgically ( n = 1; 8%). Surgical repair was necessary for the following conditions: end-organ malperfusion ( n = 9; 69%), impending rupture ( n = 3; 23%) and dilatation of the aorta with ongoing pain refractory to medical treatment ( n = 1; 8%). Overall survival at the end of the follow-up period was 71%, with 77% in the surgical group and 63% in the conservative group ( P = 0.91). Freedom from surgical intervention was 71%, with 82% in the surgical and 63% in the conservative group ( P = 0.21), and freedom from a neurological event was 88%, with 89% versus 89% ( P = 0.68) in the surgical and conservative groups, respectively. CONCLUSIONS: Aortic arch dissection is a rare pathological condition that is one of the most challenging decision-making entities. Patients manifesting an uneventful course not requiring a surgical intervention during a hospital stay were at a higher risk for aorta-related intervention during the follow-up period. The treatment modality had no impact on survival or on the incidence of a neurological event.